Pengaruh Struktur Modal, Pertumbuhan Laba, dan Ukuran Perusahaan terhadap Kualitas Laba Perusahaan Sektor Barang Konsumer Primer di Bursa Efek Indonesia - Forentina Vivi; Hengky Leon (Universitas Muhammadiyah Palembang, 2025)
This study aims to determine the effect of capital structure, profit growth, and company size on earnings quality. The type of research uses a quantitative approach with associative methods. The population of this study consists of primary consumer goods sector companies listed on the Indonesia Stock Exchange, totaling 132 companies. Sampling was carried out using criterion sampling techniques, resulting in a sample of 90 companies. Data analysis techniques used ordinary least squares with Statistical Product and Service Solution (SPSS) software version 26. Simultaneously, the feasibility of the regression model can be accepted, meaning that capital structure, profit growth, and company size influence earnings quality. Partially, company size has a negative effect on earnings quality, while capital structure and profit growth do not have an effect on earnings quality. This indicates that the scale of the company determines the quality of earnings, but the management of funding and changes in the company's earning conditions do not affect the reliability of earnings information, and there are other factors such as profitability, liquidity, and the quality of corporate governance that can influence.